Female killers and gender politics in contemporary South African crime fiction: Conversations with crime writers Jassy Mackenzie, Angela Makholwa, and Mike Nicol. (June 2017) - Binder, Sabine
Social analysis is part and parcel of South African crime fiction, 1 a genre which has been flourishing since the end of apartheid. Interrogating the country's high levels of gender-based violence, various South African crime writers explore gender issues in their fiction. 2 Critically-acclaimed crime writers Jassy Mackenzie, Angela Makholwa, and Mike Nicol stand out in this field through their creations of instantly memorable female serial killers as protagonists. In the interviews that follow, the three writers discuss the rationales behind their choice of a traditionally masculine role for their female protagonists, how they navigated through ensuing ethical problems and their characters' potential for uncomfortable reader identification, but also virulent issues of gender in contemporary South African society. They argue that since assertions of power have so long been connected to assertions of masculinity, performing the male role of the killer is a way for their female figures to move to a place of power. Thus, their protagonists' perpetrating agency enables them to be the equals — if not superiors — of the men they interact with. 3 Moreover, it empowers them to act as renegades who contest the dominant power and who are generally in control in an environment which is rife with inequality and where women more often than not are the victims of crime. In this way, besides being a means to explore female perpetrating agency, the figure of the female killer also has the potential to transform the way readers of crime fiction view women. 4